Forming mechanism of three-dimensional integral fin based on flat surface - Xiang, Jian-hua; Duan, Ji-an; Zhou, Hai-bo; Zhang, Chun-liang; Liu, Gui-yun; Zhou, Chao (Journal of Central South University, 2015)
To improve heat-transfer performance, a novel integral three-dimensional fin-structure on the plat surface was presented to increase the evaporation efficiency. The three-dimensional fin-structure is composed of a spiral micro-groove and multi radial micro-grooves. Both ploughing-extrusion (P-E) and stamping were used to form the integral-fins with a connection between radial and circumferential directions. Based on the SEM results, the relationships among P-E speed v P-E , rotational speed n p and feed f p , and among interference length L i , stamping feed angle θ c and stamping depth a c were analyzed. The effects of processing parameters on the groove morphology and the matching relationship between parameters were also discussed. The integral finned surface with micro-grooves and cracks can be obtained under such processing conditions: P-E depth a p =0.3 mm, a c =0.3 mm, the interval of helical groove d p =1.24 mm, θ c =2° and n p =50 r/min.